2018
DOI: 10.1155/2018/5451398
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Tests of Concrete Slabs Reinforced with Stainless Steel Bars

Abstract: Experimental studies on fatigue behavior of reinforced concrete slab with stainless steel rebar and carbon steel rebar have shown that, at the same reinforcement ratio, the slope of the deflection-cycle number curves of stainless steel-reinforced concrete slab is lower than that of ordinary steel-reinforced concrete slab. e higher the reinforcement ratio is, the smaller the maximum crack width would be. Higher stress level contributes to larger deflection and reinforcement strain in midspan and shorter fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Nevertheless, as stainless steel is still a relatively novel structural material especially in RC members, there has been limited research into the behaviour under cyclic loading, and the research that does exist has been quite recent. For example, Zhang et al [108] tested five RC slabs which were reinforced with either grade 1.4362 duplex SS or carbon steel rebars, and subjected to cyclic fatigue loading. It was shown that the SS reinforced concrete slabs had significantly better fatigue performance compared with carbon steel reinforced concrete slabs, including lower deflections, steel strains and crack widths as well as longer fatigue life.…”
Section: Cyclic Behaviour Of Stainless Steel Rc Membersmentioning
confidence: 99%
“…Nevertheless, as stainless steel is still a relatively novel structural material especially in RC members, there has been limited research into the behaviour under cyclic loading, and the research that does exist has been quite recent. For example, Zhang et al [108] tested five RC slabs which were reinforced with either grade 1.4362 duplex SS or carbon steel rebars, and subjected to cyclic fatigue loading. It was shown that the SS reinforced concrete slabs had significantly better fatigue performance compared with carbon steel reinforced concrete slabs, including lower deflections, steel strains and crack widths as well as longer fatigue life.…”
Section: Cyclic Behaviour Of Stainless Steel Rc Membersmentioning
confidence: 99%
“…Galvanized reinforcements have poor adhesion to concrete [ 9 ]. Stainless steel reinforcements are very costly to produce; thus, they are not widely used in the industry [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the structural behavior of SSRC has increased recently, with the focus being on the flexural performance, fatigue behavior, seismic behavior, and mechanical behavior under the impact load of SSRC [1,[22][23][24]. Rabi et al [23] established the finite element model of SSRC beams based on the existing test data.…”
Section: Introductionmentioning
confidence: 99%